L'università della terza fase - Massimo Baldacci (Firenze University Press, 2019)
The paper critically discusses the current situation of the universities in Italy characterized by a neoliberal approach. The link between the universities and the economic system is the object of the investigation of in this paper. This link identifies the main factor of competitiveness in human capital and the principle of productivity in accountability. The activity of the ANVUR (National Agency for University Rating) is part of this neoliberal framework. Furthermore, this paper examines the experimentation of the evaluation of the learning of university students (TECO).